2005
DOI: 10.1002/ijc.20972
|View full text |Cite
|
Sign up to set email alerts
|

Lithium‐mediated downregulation of PKB/Akt and cyclin E with growth inhibition in hepatocellular carcinoma cells

Abstract: We studied in vitro effects of glycogen synthase kinase 3b (GSK3b)-inhibitor lithium on the growth of hepatocellular carcinoma (HCC) cells. Lithium induced strong growth inhibition (>70%) in 75% (n = 9 of 12) of cell lines, apparently independent from the status of major genes that are mutated in HCC including p53, p16 INK4a , b-catenin and Axin1. Comparative studies with a growth-sensitive Huh7 and growth-resistant Hep40 cell lines showed that lithium induces growth arrest in Huh7 cells but not in Hep40 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 50 publications
9
50
0
5
Order By: Relevance
“…Huh7 cells express a codon 220-mutant p53, and PLC5 cells express a codon 139/161-and codon 249-mutated p53, whereas Hep3B is a p53-null cell line. Sk-hep1 has homozygous deletion of p14 ARF in the p53 pathway (34). Whereas all four HCC lines bear different types of p53 mutation, unexpectedly, bortezomib still induced differential apoptotic activities among them.…”
Section: Discussionmentioning
confidence: 93%
“…Huh7 cells express a codon 220-mutant p53, and PLC5 cells express a codon 139/161-and codon 249-mutated p53, whereas Hep3B is a p53-null cell line. Sk-hep1 has homozygous deletion of p14 ARF in the p53 pathway (34). Whereas all four HCC lines bear different types of p53 mutation, unexpectedly, bortezomib still induced differential apoptotic activities among them.…”
Section: Discussionmentioning
confidence: 93%
“…So far GSK3B has been described to be involved in modulating biological processes as opposite as proliferation or apoptosis, depending on the cellular, molecular, and developmental context (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). In fact, GSK3B is known to play an antiproliferative role by promoting APC-dependent phosphorylation-and hence proteosome-mediated degradation-of b-catenin, a transcription factor positively regulating Myc and cyclin D1 expression (14).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has been reported that lithium, an inhibitor of GSK-3ß, has anti-neoplastic effects in human melanoma, hepatocellular carcinoma, prostate cancer and glioma (7,(12)(13)(14). It is well-known that lithium mimics the activation of the Wnt pathway, leading to nuclear accumulation of ß-catenin, an independent marker of a good outcome in MB (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Although some of these data may be debatable, the idea is thus raised that lithium may have antitumor properties. These effects are however cell-type dependent: on the one hand, lithium stimulates cell proliferation in mammary tumour cells (11), and on the other, it inhibits cell proliferation in melanoma (12), hepatocellular carcinoma (13) and prostate cancer (7), and it blocks glioma cell migration and invasion in vitro (14). Lithium chloride can also induce apoptosis in several cell types (8,15), even if it has been reported to have anti-apoptotic, especially neuroprotective, effects in certain experimental settings (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%